Evidence of opposing fitness effects of parental heterozygosity and relatedness in a critically endangered marine turtle?. (28th August 2017) - Phillips, K. P.; Jorgensen, T. H.; Jolliffe, K. G.; Richardson, D. S.
Abstract: How individual genetic variability relates to fitness is important in understanding evolution and the processes affecting populations of conservation concern. Heterozygosity–fitness correlations (HFCs) have been widely used to study this link in wild populations, where key parameters that affect both variability and fitness, such as inbreeding, can be difficult to measure. We used estimates of parental heterozygosity and genetic similarity ('relatedness') derived from 32 microsatellite markers to explore the relationship between genetic variability and fitness in a population of the critically endangered hawksbill turtle, Eretmochelys imbricata . We found no effect of maternal MLH (multilocus heterozygosity) on clutch size or egg success rate, and no single‐locus effects. However, we found effects of paternal MLH and parental relatedness on egg success rate that interacted in a way that may result in both positive and negative effects of genetic variability. Multicollinearity in these tests was within safe limits, and null simulations suggested that the effect was not an artefact of using paternal genotypes reconstructed from large samples of offspring. Our results could imply a tension between inbreeding and outbreeding depression in this system, which is biologically feasible in turtles: female‐biased natal philopatry may elevate inbreeding risk and local adaptation, and both processes may be disrupted by male‐biased dispersal. Although this conclusion should be treated with caution due to a lack of significant identity disequilibrium, our study shows the importance of considering both positive and negative effects when assessing how variation in genetic variability affects fitness in wild systems.